Práticas Sociais Religiosas: um estudo sociológico pontual - José Ivo Follmann; Adevanir Aparecida Pinheiro (Ciências Sociais Unisinos)
This paper explores the concept of Religious Social Practices (RSP) and presents a synthesis of the main results of a research conducted by the authors about these practices in some cities of the Sinos River Valley in the Metropolitan Area of Porto Alegre, Brazil. The research contains a triple approach to RSP, taking into consideration the production of society as a whole, the fields of activity and the personal dynamics of the subjects and their identities. Besides reporting on the main results of the research project, the article points out some hypothesis and suggestions for further studies involving institutional, ideological, political and subjective processes.